Kemudahan Penggunaan Sistem Informasi Akuntansi Memoderasi Pengaruh Kemampuan Teknis Pengguna Dan Kecerdasan Intelektual Pada Kinerja Karyawan - Antari, Ni Putu Riska; Widhiyani, Ni Luh Sari (E-Jurnal Akuntansi, 2024)
The study aims to empirically examine the relationship between user technical ability and intellectual intelligence on employee performance at the Bangli Regency People's Economic Bank with the ease of use of accounting information systems as a moderating variable. The study population included all employees of BPR Bangli Regency totalling 134 people, with 52 people involved in terms of AIS. The sampling method is nonprobability sampling with purposive sampling technique. The data were analysed using the Moderated Regression Analysis (MRA) technique. The results showed that user technical ability had no effect on employee performance and intellectual intelligence had a positive influence on employee performance. Ease of use of AIS is also proven to be able to moderate the influence of these two factors on employee performance.